الاعتقال في السياسة الإسرائيلية في القوانين والمواثيق الدولية - مزهر، وليد عبدالرحمن (مركز جيل البحث العلمي, 2017)
تعتبر المواثيق الدولية حركة المقاومة الفلسطينية في حالة دفاع عن النفس أثر الهجوم الصهيوني الذي وقع عليها منذ عام 1948م والمستمر إلى يومنا هذا، ما تضمنته اتفاقية جنيف الثالثة لسنة 1949م وكذلك اتفاقية لاهاي سنة 1899م وسنة 1907م. وفي صدد ذلك أصدرت الأمم المتحدة وخاصة الجمعية العامة قرارات عدة بإسباغ حماية أسرى الحرب على حركات التحرير ورجال المقاومة. يجب أن يعامل أفراد المقاومة الفلسطينيين الذين يقعون في أسر قوات الاحتلال كأسرى حرب وأن يتمتعوا بكافة الامتيازات المعطاة لهم بموجب المواثيق الدولية وخاصة اتفاقية جنيف لعام 1949م إلا أن سلطات الاحتلال تسعى جاهدة إلى حرمانهم من أبسط حقوقهم ولقد أعلنت منظمة التحرير الفلسطينية بالتزامها باتفاقية جنيف كما أن عدم اعتراف أحد أطراف النزاع بالطرف الأخر لا يعتبر مانعاً من انطباق الاتفاقية ذلك لأن الاعتراف نسبي حيث أن الدول العربية التزمت بتطبيق هذه الاتفاقية رغم عدم اعترافها بإسرائيل إلى جانب عدد كبير من دول العالم التي لم تعترف بها وذلك على نقيض منظمة التحرير الفلسطينية التي اكتسبت اعترافاً دولياً من عدد من دول العالم، وكذلك الاعتراف الإسرائيلي في واشنطن بمنظمة التحرير الفلسطينية كممثل شرعي وحيد للشعب الفلسطيني، وأخيراً الاعتراف بفلسطين كعضو مراقب في الجمعية العامة للأمم المتحدة. سنتبع في هذه الدراسة أسلوب المنهج الوصفي التحليلي على أساس قراءة واقع الممارسات الإسرائيلية ومدى التزامها بالمواثيق الدولية المنظمة لحقوق الأسرى. تكمن مشكلة البحث في الإجابة عل السؤال الرئيس التالي: هل الممارسات الإسرائيلية بحق الأسرى الفلسطينيين تتفق مع القوانين والمواثيق والأعراف الدولية؟
The international charters consider the Palestinian Resistance as in self-defense due to the impact of the Zionist attack that was signed since 1948 and continues to this day ، as contained in the Third Geneva Convention of 1949 as well as The Hague Convention in 1899 and 1907 ، and in this regard the United Nations and the General Assembly issued several resolutions to confer protection of prisoners of war on liberation movements and resistance. The Palestinian resistance members who are captured by the occupying forces must be treated as prisoners of war and enjoy all the privileges granted them under the international conventions ، especially the Geneva Convention of 1949. However ، the occupation authorities strive to deprive them of their most basic rights. The PLO declared its commitment to the Geneva Convention ، one of the parties to the conflict recognize the other party is not considered an obstacle to the applicability of the Convention ، because the relative recognition as the Arab states committed to the application of this Convention ، despite the lack of recognition of Israel as well as a large number of countries in the world that did not recognize it as the antithesis of the Organization Palestinian liberation that has gained international recognition from a number of countries of the world ، as well as the recognition of Israel in Washington ، the PLO as the sole legitimate representative of the Palestinian people ، and finally the recognition of Palestine as an observer in the General Assembly of the United Nations. In this study the descriptive analytical method is being used and would be based on monitoring the reality of Israeli practices and the extent of its commitment to international conventions for prisoners' rights organization. The problem search is in the answer to the following question: Is the Israeli practices against Palestinian prisoners in line with international laws and conventions and norms?
Keywords: المواثيق الدولية -- القوانين والتشريعات -- المقاومة الفلسطينية -- الاحتلال الصهيونى -- السياسة الإسرائيلية